(untitled) (Research, Society and Development, 2022)
The elaboration of this article presents the results of a bibliographic research whose general objective was to present reflections on the impact of compliance programs and compliance management on the structure and performance of governance, mapping the success factors. After selecting the works that constituted the revised sources, a content analysis was carried out guided by the following structuring thematic categories: foundations of corporate governance, compliance and interconnection; structuring aspects of compliance management (instrumental dimension); risk mitigation; interface between management instruments and the internal control apparatus. This survey resulted in the observation, from an instrumental perspective, of the continence relationship between the concepts of corporate governance, compliance management and the Compliance and Integrity Program. Directive documents, policies, internal controls, processes, procedures and protocols are human products. Adherence to organizational directives, rather than conditioned responses, needs to produce conscious and spontaneous adherence. The greater the adherence and organizational engagement to the leadership commands, the more effective the internal controls, the lower the number of occurrences of deviant or even illegal behavior. From the arguments presented, the importance of these Programs, or in an expanded sense, of compliance management, for the institution of a responsive, efficient, effective and socially responsible governance environment remained evident.